Pengaruh Akuntabilitas, Transparansi, Pengendalian Intern, Dan Sistem Informasi Akuntansi Terhadap Efektivitas Pengelolaan Anggaran Di Badan Pengelolaan Keuangan Dan Aset Daerah Kota Surabaya - Sabrina Nova Ashara; Muhammad Taufik Hidayat (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Effective regional financial management is one of the main indicators in achieving good governance. Accountability, transparency, internal control and accounting information systems have a very important role in ensuring that budgets are managed efficiently, on target and in accordance with applicable regulations. This research aims to examine the influence of accountability, transparency, internal control and accounting information systems on the effectiveness of budget management in the Surabaya City Regional Financial and Asset Management Agency. This research uses a quantitative approach with primary data collected through questionnaires distributed to BPKAD employees in the city of Surabaya. Data analysis was carried out using SPSS version 30 software. The research results revealed that accountability, transparency, internal control and accounting information systems significantly influence the effectiveness of budget management. It is hoped that these findings can become a reference for local governments in efforts to improve the quality of regional financial management to support the creation of good governance.